2017
DOI: 10.29300/nuansa.v10i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Media Sosial Terhadap Paham Radikalisme

Abstract: The purpose of this paper is to see the impact of social media on the idea of radicalism. In writing this paper using literature study method. And from the description in this paper can be concluded that social media have a positive and  negative impact. The negative impact of the free use of social media is the ease of accepting the Indonesian public receiving information including radicalism from all fields without finding out the truth of this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
6
0
6
Order By: Relevance
“…The data from the Ministry of Communication and Informatics revealed that there were 800.000 Indonesian sites which were indicated as the hoax and hate speech spreaders. The fact confirms that the social media has the potency to spread the radicalism virus even separatism over the Unitary State of the Republic of Indonesia (Sunarto, 2017).…”
Section: Introductionmentioning
confidence: 59%
“…The data from the Ministry of Communication and Informatics revealed that there were 800.000 Indonesian sites which were indicated as the hoax and hate speech spreaders. The fact confirms that the social media has the potency to spread the radicalism virus even separatism over the Unitary State of the Republic of Indonesia (Sunarto, 2017).…”
Section: Introductionmentioning
confidence: 59%
“…Berkembangnya teknologi membawa perubahan pada tatanan kehidupan manusia. (Sunarto, PhD, 2017 Menghadapi "Era Disrupsi Teknologi" yang terpenting adalah kepemimpinan.…”
Section: Pendahuluanunclassified
“…Dapat melibatkan interaktivitas pelajar/I yang tinggi. Media sosial yang digunakan pelajar memfasilitasi komunikasi, interaksi, saling kirim pesan, dan saling berbagi (sharing), dan membangun jaringan/networking (Sunarto, 2017).…”
Section: Pendahuluanunclassified